MECHANISMS AND OUTCOMES OF 1470NM LASER THERAPY FOR VAGINAL REJUVENATION: A MULTI-OMICS OBSERVATIONAL STUDY - Smit Bharat Solanki; Dutta, Deblina (Universitas Airlangga, 2025)
Highlights: Multi-omics analysis revealed significant upregulation of genes and proteins linked to collagen remodeling and angiogenesis after 1470nm laser therapy. The study provides the first integrated clinical and molecular evidence demonstrating the mechanistic role of TGF-β signaling in vaginal tissue regeneration following laser treatment. Abstract: Introduction: Vaginal laxity and compromised vascularization significantly impact women’s quality of life, especially post-childbirth and during menopause. Non-invasive therapies, such as 1470nm laser technology, stimulate collagen production and enhance tissue regeneration. This study hypothesizes that 1470nm laser therapy improves vaginal health through collagen remodeling and neovascularization, supported by multi-omics data elucidating key biological pathways. Methods: This prospective observational study enrolled 120 women aged 25–65 years with symptoms of vaginal laxity, dryness, or decreased elasticity. Participants underwent 3–5 sessions of 1470nm laser therapy. Clinical outcomes were assessed using high-resolution ultrasound, optical coherence tomography (OCT), histopathology, and patient-reported outcomes (FSFI, PGI-I). Multi-omics integration included RNA sequencing, proteomics, and metabolomics. Results: Vaginal wall thickness increased by 35% (p<0.001), and collagen density improved by 42% (p<0.001). FSFI scores rose by 28% (p<0.001), with 92% of women reporting improved sexual satisfaction. Molecular analyses showed upregulation of collagen synthesis and angiogenesis-related genes (COL1A1, COL3A1, VEGF, FGF), with TGF-β signaling emerging as a key regulatory pathway. Conclusion: 1470nm laser therapy significantly improves vaginal structure and function with a favorable safety profile. This study uniquely integrates clinical outcomes with multi-omics data, offering novel mechanistic insights and supporting its role in personalized regenerative gynecology.